THE INFLUENCE OF HOSPITAL MANAGEMENT POLICY INNOVATION (X) ON CLINICAL SERVICE QUALITY (Z) WITH INTER-UNIT COORDINATION (Y) AS A MEDIATING VARIABLE - Mega Inang Marsalina Sarata; Greatavia Meanda Leslie; Vip Paramarta (RADJA PUBLIKA, 2025)
Hospitals, as healthcare service organizations, face the challenge of continuously improving the quality of clinical services amid the dynamic needs of patients and the complexity of health systems. Management policy innovation is seen as a strategic instrument to address these challenges; however, its effectiveness often depends on how well inter-unit coordination is carried out. This study aims to analyze the effect of hospital management policy innovation on the quality of clinical services, with inter-unit coordination as a mediating variable, through a literature review approach. The research method employs library research by reviewing various scholarly sources such as reputable journal articles, books, and relevant official reports. The findings indicate that management policy innovations such as the digitalization of health information systems, strengthening of clinical governance, and patient safety policies positively influence improvements in clinical service quality. Nevertheless, this influence becomes more optimal when supported by effective cross-unit coordination, which includes the integration of service flows, team communication, and risk control. In conclusion, inter-unit coordination serves as an important mediator that strengthens the impact of management policy innovations on the quality of clinical services. Therefore, hospitals should prioritize cross-unit synergy in the implementation of every innovative policy.